Comparison of Active and Passive Humidifiers on Mechanical Ventilation - H. Dilek Mersin Özcanoğlu; Seval Ürkmez; Oktay Demirkıran; Tuğhan Utku; Yalım Dikmen (Galenos Yayinevi, 2010)
Objective: To research the effectiveness on humidifying, respiratory mechanics, bacterial colonization and infection rates of continuous usage for 96 hours of active and passive humidifiers which are used for heating and moisturizing the inspired gases in patients under mechanical ventilation. Materials and Methods: Adult patients who are expected to support at least 4 days under mechanical ventilation, excluding patients with primary lung disease and sepsis, are included in the research. Patients are separated in two groups as a passive humidifier group (heat moisture exchange filter) (n=16) and an active humidifier group (n=14). In passive humidifier group, humidifier is used continuously for 96 hours without change. In active humidifier group moisturizing is obtained by using sterile distilled water in heated humidifier. Patients whose demographic characteristics were recorded and first 24 hour APACHE II scores were calculated, were taking chest X-Ray's daily. Respiratory mechanics measurements were recorded twice a day which were watched in Servo300A ventilators respiratory mechanics monitor, in patients under volume controlled ventilation. The amount of moisture and liquidity of the secretion in endotracheal tube were recorded and scored visually. The endotracheal aspiration samples at the beginning and at the end of 96th hour and respiratory circuits ventilator side sample taken at 96th hour were studied microbiologically. Cultures and colonial counts were studied at Cerrahpasa Medical Faculty Microbiology Laboratory. Results: There were no significant difference in two groups by demographic data, APACHE II scores and illness diagnoses. In passive humidifier group, respiratory mechanics showed no significant difference between the beginning and the 4th day (p>0.05). In active humidifier group when MAP, PEEPtot, EEF, Rins, Rexp values showed no significant difference between the beginning and the 4th day but PIP values showed significant differences between 3rd and 4th day, dynamic compliance value showed significant differences between first and 3rd - 4th day and first-4. day (p>0.05). Each two groups showed no difference in moisturizing and secretion density (p>0.05).There was no endotracheal occlusion in any patients. There were no significant differences in bacteriological studies of endotracheal aspirate and circuit samples taken from patients in both groups. Conclusion: Our findings showed that passive humidifiers used for 96 hours without changed, do not loose their effectiveness and do not increase airway resistance and end-expiratory flow and do not cause bacterial colonization. (Journal of the Turkish Society of Intensive Care 2010; 8: 54-60)